Strategi Peningkatan Ekonomi dan Tinjauan Ekonomi Islam Masa Covid 19 (Studi Kasus: UMKM di Kota Medan) - Marliyah Marliyah; Zuhrinal M Nawawi; Jihan Humairoh (ITB AAS INDONESIA Surakarta, 2022)
MSME (Micro Small and Medium Enterprises) are able to create jobs faster than large businesses. Micro, small and medium enterprises can also contribute to exports and trade so that they become one of the supporters of the country's foreign exchange even though the contribution of MSME is smaller. This research method is qualitative using SWOT analysis. The results show that the strategies used by SO (Strength–Opportunity) are: Making human resources who are responsible, hardworking and honest so that micro, small and medium enterprises can develop well. Maintain a harmonious relationship between owners and employees so that employee performance is of higher quality and can produce a positive impact on micro, small and medium enterprises. Utilize e-commerce features to get a broad target market during the Covid-19 period. Focus on one line of business so that MSME get targets according to what is expected. And continue to provide creative ideas and execute them during the Covid-19 pandemic in order to minimize the challenges that come. In the view of Islamic economics, that micro-enterprises have a divine influence, remembering the basics of their arrangement which were not laid down by Allah SWT, having the dimensions of faith, character, morals and the Al-Quran and Hadith as sources of economic principles.